La tradición clásica en Debate entre un cristiano y un judío, Los diez mandamientos, Libro de los doce sabios y Libro de los cien capítulos - Santana Henríquez, Germán (Fortunatae: Revista canaria de Filología, Cultura y Humanidades Clásicas, 2011)
This paper attempts to show the Graeco-Roman Classical Tradition in four anonymous works from the 13th century. The first two works present a direct language with dialogues and are very short because as they address an audience that is illiterate in practical terms. The other two, however, can be categorized as Castilian Sapiential prose, and are structured in terms of maxims. These works came to be true handbooks of good conduct among noblemen and vassals.